Metabolomic profiling of varicocele-induced male infertility: insights from spermatic vein blood analysis - Wei, Xiyi; Yu, Zijie; Wang, Shuai; Zhong, Da; Wang, Yichun; Zhang, Xi; Shao, Wenchuan; Yan, Xinghan; Qin, Chao; Song, Ninghong (Frontiers in Endocrinology, 2026)
ObjectiveVaricocele (VC) is a leading cause of male infertility, but its pathophysiological mechanisms remain inadequately defined. This study aimed to characterize metabolic alterations in spermatic vein blood of varicocele patients with/without infertility (VI/VF groups) compared to healthy donors.MethodsWe collected spermatic vein blood samples from VC patients and peripheral blood samples from healthy donors. VC patients scheduled for surgery were categorized into VF (without infertility) group or VI (with infertility) group based on fertility status, with healthy donors as the negative control (NC) group. Metabolic profiling of spermatic vein blood from VC patients and peripheral blood from healthy donors was performed using liquid chromatography-mass spectrometry (LC-MS). Semen parameters and ultrasound findings were recorded. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were employed to identify metabolic differences, followed by pathway enrichment analysis.ResultsA total of 40 VC patients and 35 healthy donors were included in this study. Semen quality in the VI group was significantly compromised compared to VF and NC groups (P < 0.001). Metabolic profiling revealed profound alterations in varicose spermatic veins of VC groups, including upregulated steroid hormone biosynthesis, disrupted amino acid and energy metabolism, and elevated reactive oxygen species (ROS) production compared to healthy donors. Differences between VI and VF groups were primarily localized to the alanine, aspartate, and glutamate pathway, with γ-aminobutyric acid, succinic acid, and aspartate significantly upregulated in VI groups (P < 0.05). Among renal and adrenal metabolites, only calcitroic acid exhibited differential expression (P < 0.01), while oxidative stress markers, including N-acetylcysteine and acylcarnitines (P < 0.05), showed significant variation.ConclusionUntargeted metabolomics highlighted D-aspartic acid overexpression as a potential contributor to infertility in VC patients. This study provided only limited support for the retrograde reflux theory of renal and adrenal metabolites, while offering additional evidence consistent with the oxidative stress hypothesis. Oxidative stress-related metabolites may represent potential candidate diagnostic and therapeutic targets for VC-induced infertility.